2021
DOI: 10.1002/hep.31644
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death Ligand 1 Is Overexpressed in Liver Macrophages in Chronic Liver Diseases, and Its Blockade Improves the Antibacterial Activity Against Infections

Abstract: Objective: Bacterial infections are common and severe in cirrhosis, but its pathogenesis is poorly understood. Dysfunction of liver macrophages may play a role, but information about their function in cirrhosis is limited. Aims were to investigate the specific profile and function of liver macrophages in cirrhosis and their contribution to infections. Design: Macrophages from human cirrhotic livers were characterized phenotypically by transcriptome analysis and flow cytometry; function was assessed in vivo by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…We also found up-regulated PD-1 and PD-L1 expression of peripheral monocytes and lymphocytes in patients with ALF and increased plasma soluble PD-L1 levels predicting mortality and development of sepsis (227). Similarly, another study demonstrated overexpression of PD-L1 in peripheral monocytes and liver macrophages in cirrhotic patients who displayed impaired hepatic bacterial uptake (228). Interestingly, monocyte PD-L1 was associated with disease severity and infection risk in cirrhosis while anti-PD-L1 mAb treatment restored the phagocytic capacity of macrophages and reduced bacterial dissemination in mice with chronic liver injury (228).…”
Section: E Macrophage Regulation Via Immune Checkpoint Blockadesupporting
confidence: 64%
See 1 more Smart Citation
“…We also found up-regulated PD-1 and PD-L1 expression of peripheral monocytes and lymphocytes in patients with ALF and increased plasma soluble PD-L1 levels predicting mortality and development of sepsis (227). Similarly, another study demonstrated overexpression of PD-L1 in peripheral monocytes and liver macrophages in cirrhotic patients who displayed impaired hepatic bacterial uptake (228). Interestingly, monocyte PD-L1 was associated with disease severity and infection risk in cirrhosis while anti-PD-L1 mAb treatment restored the phagocytic capacity of macrophages and reduced bacterial dissemination in mice with chronic liver injury (228).…”
Section: E Macrophage Regulation Via Immune Checkpoint Blockadesupporting
confidence: 64%
“…Similarly, another study demonstrated overexpression of PD-L1 in peripheral monocytes and liver macrophages in cirrhotic patients who displayed impaired hepatic bacterial uptake (228). Interestingly, monocyte PD-L1 was associated with disease severity and infection risk in cirrhosis while anti-PD-L1 mAb treatment restored the phagocytic capacity of macrophages and reduced bacterial dissemination in mice with chronic liver injury (228). These studies indicate that immune checkpoint blockade may be an effective and safe strategy for restoration of defective antibacterial responses in chronic liver failure patients, where conventional treatment options are currently very limited.…”
Section: E Macrophage Regulation Via Immune Checkpoint Blockadementioning
confidence: 83%
“…This immune dysfunction includes reduced components of the complement system, macrophage activation, impaired lymphocyte and neutrophil function, Tolllike receptor upregulation, and intestinal dysbiosis 9,79 . Although research attention has mostly focused on mechanisms leading to severe bacterial infection 80 , CAID has also been shown to predispose to a variety of viral or fungal-related disease 81 . Whether patients with CLD and cirrhosis are more susceptible to SARS-CoV-2 infection has been the focus of much attention throughout 2020.…”
Section: Sars-cov-2 Infection and Liver Disease Clinical Course And Omentioning
confidence: 99%
“…On the other hand, the persistent activation of hepatic macrophages may result in immune exhaustion, a scenario with inefficient and immunosuppressive macrophages which are unable to phagocyte pathogens, and which are associated with an increased risk of infections in patients [123]. Indeed, the blocking of PD-L1 (a marker of macrophage exhaustion) improved macrophage function in an animal model of chronic liver injury [123], suggesting that achieving an anti-inflammatory but also functional macrophage phenotype is of importance for CLD, and should be a matter of future study. For this reason, and considering their interactions with the other sinusoidal cells during liver injury, KCs are being studied as therapeutic targets for different liver diseases [107,108].…”
Section: Kupffer Cells In Cldmentioning
confidence: 99%
“…In this regard, during CLD, the sinusoidal microenvironment rich in proinflammatory cytokines and ROS, alone or in combination with the source of liver injury (e.g., alcohol, a virus, excessive lipids) may induce increased DNA damage and promote de novo carcinogenesis [256,257]. Furthermore, the suppressed state of the immune system during CLD may contribute to the altered removal of dysfunctional cells [123,[258][259][260], further enhancing tumour initiation.…”
Section: Cld and The Sinusoidal Microenvironment In The Development Of Hccmentioning
confidence: 99%